Position Paper of the Department of Hypertension of the Brazilian Society of Nephrology: Use of renin-angiotensin system blockers during the course of Covid-19 infection - Cibele Isaac Saad Rodrigues (Brazilian Journal of Nephrology, 2020)
ABSTRACT This position statement of the Department of Hypertension of the Brazilian Society of Nephrology (SBN) addresses the controversy surrounding the use or suspension/replacement of the renin-angiotensin-aldosterone system blockers (particularly inhibitors of the angiotensin-converting enzyme or angiotensin II AT1 receptor blockers) prophylactically in individuals using these drugs, due to the possibility of allegedly worsening the prognosis of hypertensive patients infected with SARS-CoV-2. The SBN Hypertension Department recommends individualizing treatment and maintaining these medications until better scientific evidence is available.